Implementation of Augmented Reality for Javanese Script Recognition Using FAST Corner Detection Algorithm - Sukma Kanugrahan, Panji; Aditia Gerhana, Yana; Rauda Ramdania, Diena (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
The aim of this research is to design and develop an Augmented Reality (AR) application to help junior high school students learn and recognize Aksara Jawa by leveraging the FAST Corner Detection algorithm and Marker-Based Tracking techniques to enhance interactivity and engagement. Using AR technology, students can explore Aksara Jawa characters in an engaging way, with 3D objects displayed in real time as they scan designated markers. The research methodology involves literature review, observation, and interviews with educators, while the application development follows the Multimedia Development Life Cycle (MDLC) to ensure quality. Testing shows the application accurately detects markers and displays 3D objects for the intended characters, and feedback from both teachers and students confirms its effectiveness and appeal. Further development of features and content is recommended to make the application even more beneficial and aligned with the needs of Aksara Jawa language education.